Palladium-based bimetallic nano-catalyst as well as preparation method and application thereof
By using palladium-based bimetallic nanocatalysts in the carbon dioxide hydrogenation reaction, using a two-step reduction method and a TiO2 support, the existing palladium-based catalysts have been solved, and efficient carbon dioxide conversion and selectivity of low-carbon mixed alcohols have been achieved.
Patent Information
- Application Number
- CN202411981070.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the existing carbon dioxide hydrogenation reaction, the carbon dioxide conversion rate of palladium-based catalysts is relatively low, the main products are methanol, methane and carbon monoxide, and the selectivity of low-carbon mixed alcohols is relatively low.
The palladium-based bimetallic nanocatalyst is prepared by a two-step reduction method. The types and ratios of palladium and the second metal are regulated to improve the activity and selectivity of the catalyst.
The conversion rate of carbon dioxide and the selectivity of low-carbon mixed alcohols have been significantly improved, which has significantly improved compared with traditional catalysts, achieving controllable generation from methanol to low-carbon alcohols.
Smart Images

Figure CN119897130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide hydrogenation catalyst preparation, and in particular to a palladium-based bimetallic nanocatalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of industrialization, carbon dioxide (CO2) produced by the excessive use of fossil energy has seriously affected human survival and social development. On average, tens of billions of tons of carbon dioxide are emitted into the atmosphere every year, resulting in a rapid increase in the carbon dioxide content in the atmosphere, posing a great threat to the ecosystem, such as climate warming, glacier melting and ocean acidification. Therefore, reducing carbon dioxide emissions and ensuring sustainable development are urgent tasks. From the perspective of long-term development, the conversion of carbon dioxide into high-value-added chemical products through chemical conversion can achieve a sustainable artificial carbon cycle, which has been recognized as an effective, profitable and promising solution while reducing dependence on fossil fuels. At present, the chemical products produced by the hydrogenation of carbon dioxide include carbon monoxide, methane, methanol, ethanol, olefins, etc.
[0003] Among them, low-carbon alcohols (methanol, ethanol and propanol) are highly valued due to their high calorific value and wide application. For example, the volumetric energy density of methanol is 15.6 MJ / L, which is about half of diesel (38.6 MJ / L) and gasoline (34.2 MJ / L). It can be used as an additive or substitute for gasoline in internal combustion engines (ICE) to improve the octane number. Compared with ordinary gasoline internal combustion engines, methanol internal combustion engines have much lower hydrocarbon, nitrogen oxide, sulfur oxide and smoke emissions, making them a high-quality diesel fuel substitute and household gas. Ethanol is considered to be an excellent fuel additive, disinfectant and solvent, and is one of the most valuable chemical products in chemical synthesis, with great demand. Traditional ethanol synthesis methods include natural raw material fermentation and ethylene hydration. With the continuous growth of population, the traditional production model can no longer meet the needs of production and life, so it is urgent to explore a low-consumption, large-scale production of ethanol to solve practical needs. Therefore, as an effective way to mitigate the greenhouse effect, the use of carbon dioxide hydrogenation to convert into low-carbon alcohols has important practical significance.
[0004] Palladium is the most commonly used hydrogenation catalyst. Its hydrogen activation ability is much higher than that of copper and other metal catalysts, and it has excellent stability and anti-sintering and anti-poisoning properties. Therefore, palladium-based supported catalysts are widely used in the research of carbon dioxide hydrogenation. Chinese patent CN101444731A discloses a palladium-zinc catalyst supported by carbon nanotubes. The catalyst is prepared by coprecipitation method with carbon nanotube-based materials as promoters, and is applied to the reaction of carbon dioxide hydrogenation to methanol. However, the carrier / promoter used in the catalyst is limited to carbon nanotube-based materials, and the preparation process is relatively complicated and cumbersome, and the cost is high. Chinese patent CN113083296A discloses a palladium / boron catalyst supported by zirconium oxide. The catalyst generates high-energy electrons and ions through plasma synergistic catalyst technology to bombard the catalyst surface, promote the decomposition of the catalyst precursor, and then prepare the catalyst. However, the reaction products of the catalyst are mainly methane and carbon monoxide. Chinese patent CN113145113A discloses a palladium-doped metal oxide solid solution catalyst. The catalyst is prepared by a co-precipitation method using a zinc-zirconium oxide solid solution as a carrier, but the carbon dioxide conversion rate of the catalyst is low, and the liquid phase products are mainly methanol and carbon monoxide.
[0005] In summary, in the current carbon dioxide hydrogenation reaction, the main problem of palladium-based catalysts is the low carbon dioxide conversion rate, and the main products of the reaction are still methanol, methane and carbon monoxide, and the selectivity of low-carbon mixed alcohols is low. Therefore, the development of new palladium-based catalysts to achieve efficient hydrogenation of carbon dioxide, while achieving the controllable generation of products from methanol to low-carbon alcohols, broadening the application field of palladium-based catalysts in carbon dioxide hydrogenation reactions, and further improving the high added value of reaction products not only has academic research value, but also has important economic benefits and application value. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a catalyst for preparing low-carbon mixed alcohols by hydrogenation of carbon dioxide, and a preparation method and application thereof. The catalyst prepared by the method of the present invention has a high conversion rate of carbon dioxide in the reaction of preparing low-carbon mixed alcohols by hydrogenation of carbon dioxide, and a high selectivity for low-carbon mixed alcohols.
[0007] One of the purposes of the present invention is to provide a method for preparing a palladium-based bimetallic nanocatalyst.
[0008] The second purpose of the present invention is to provide a palladium-based bimetallic nanocatalyst prepared by the preparation method.
[0009] The third object of the present invention is to provide an application of the palladium-based bimetallic nanocatalyst.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] In a first aspect, the present invention provides a method for preparing a palladium-based bimetallic nanocatalyst, comprising the following steps:
[0012] S1. Dissolve the TiO2 carrier and the metal M precursor in a solvent to obtain solution A, wherein the content of M ions is 1wt%-5wt% based on the mass of the TiO2 carrier, and M is one of Cu, Zn, and Fe; dissolve the reducing agent in water to obtain solution B; add solution B dropwise to solution A, stir, and obtain solution C;
[0013] S2, dissolving a palladium precursor in a solvent to obtain a solution D, wherein the content of palladium ions is 0.5wt%-1wt% based on the mass of the TiO2 carrier; adding solution D dropwise to solution C, stirring, to obtain a mixed solution;
[0014] S3, washing and drying the obtained mixed solution to obtain a palladium-based bimetallic nanocatalyst.
[0015] The catalyst of the present invention is prepared by a two-step sequential reduction method. First, a metal M precursor is reduced to metal nanoparticles by a reducing agent and deposited on a titanium dioxide carrier. Then, a palladium precursor is further reduced to palladium nanoparticles to obtain a palladium-based bimetallic nanocatalyst.
[0016] Step S1:
[0017] There is no particular limitation on the source of the TiO2 carrier, which can be purchased from the market or prepared by methods known in the art.
[0018] In some embodiments, in step S1, the average particle size of the TiO2 carrier is 20-40 nm.
[0019] In some embodiments, in step S1, when M is Cu, the copper precursor is one or more of copper nitrate, copper chloride, copper sulfate, copper acetylacetonate, copper acetate or hydrates thereof;
[0020] When M is Zn, the zinc precursor is one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or hydrates thereof;
[0021] When M is Fe, the iron precursor is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric acetate or hydrates thereof;
[0022] In some embodiments, in step S1, the solvent is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol.
[0023] In some embodiments, in step S1, the reducing agent is one or more of ascorbic acid, ammonia borane complex, diborane, ethylene glycol, sodium borohydride, potassium borohydride, and hydrazine hydrate;
[0024] The concentration of the reducing agent in solution B is 0.2-3 mol / L.
[0025] In some embodiments, in step S1, the ratio of the molar amount of the reducing agent to the total molar amount of M ions and palladium ions is 20:1 to 10:1.
[0026] In some embodiments, in step S1, the dropping speed is 0.3 to 1 mL / min, the stirring speed is 500 to 1200 r / min, and the stirring time is 0.5 to 3 h.
[0027] Step S2:
[0028] In some embodiments, in step S2, the palladium precursor is one or more of palladium acetate, palladium chloride, palladium nitrate, palladium acetylacetonate, and potassium tetrachloropalladate.
[0029] In some embodiments, in step S2, the solvent is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol.
[0030] In some embodiments, in step S2, the dropping speed is 0.3 to 1 mL / min, the stirring speed is 500 to 1200 r / min, and the stirring time is 0.5 to 3 h.
[0031] Step S3:
[0032] In some embodiments, in step S3, the washing method is centrifugal washing with deionized water and anhydrous ethanol for 3 to 8 times respectively;
[0033] The drying temperature is 50-120°C and the drying time is 12-24 hours.
[0034] In a second aspect, the present invention provides a palladium-based bimetallic nanocatalyst prepared by the above-mentioned preparation method, wherein the palladium-based bimetallic nanocatalyst comprises a TiO2 carrier, and bimetallic nanoparticles loaded on the TiO2 carrier, wherein the bimetallic nanoparticles are Pd and M, and M is one of Cu, Zn, and Fe; and the average particle size of the bimetallic nanoparticles is 3-10 nm;
[0035] Based on the mass of the TiO2 carrier, the loading amount of Pd is 0.5wt%-1wt%, and the loading amount of M is 1wt%-5wt%.
[0036] In a third aspect, the present invention provides an application of the above-mentioned palladium-based bimetallic nanocatalyst in the preparation of low-carbon mixed alcohols by catalytic reaction of carbon dioxide hydrogenation.
[0037] Preferably, the catalytic reaction is carried out in a high-pressure fixed-bed continuous flow reactor, and the reaction conditions are: reaction temperature of 200-400°C, reaction pressure of 2-8MPa, total space velocity of feed gas of 2000-7000mL / g / h, volume ratio of hydrogen to carbon dioxide of 4:1-1:1, and the low-carbon mixed alcohols are methanol, ethanol and propanol.
[0038] Preferably, the palladium-based bimetallic nanocatalyst needs to be reduced before use, the reduction treatment atmosphere is hydrogen, the hydrogen space velocity is 6000-20000 mL / g / h, the reduction treatment temperature is 200-400° C., and the reduction treatment time is 2-6 h.
[0039] Technical effects:
[0040] (1) The palladium-based bimetallic catalyst prepared by the present invention includes palladium copper, palladium zinc and palladium iron catalysts, which have a simple preparation method, a convenient operation process and a wide range of applicability;
[0041] (2) The palladium-based bimetallic catalyst prepared by the present invention has high carbon dioxide hydrogenation activity and high atomic utilization rate. By adjusting the type and ratio of palladium and the second metal, the distribution of low-carbon mixed alcohol products can be selectively regulated;
[0042] (3) The catalyst of the present invention adopts a two-step sequential reduction method. By depositing palladium atoms on the surface of the second metal, a high dispersion of palladium and regulation of the surface electronic structure of palladium can be achieved. However, changing the reduction order will cause the second metal to cover the surface of the palladium and thus reduce the catalytic reaction activity. Therefore, the reduction order in the present invention is crucial for the preparation of high-performance catalysts.
[0043] (4) The present invention utilizes the strong interaction of the metal carrier to achieve a highly dispersed distribution of the second metal on the titanium dioxide carrier, and further uses the highly dispersed second metal as a "dispersant" to achieve a highly dispersed distribution of palladium atoms by regulating the reduction rate of palladium ions, which reduces the activation ability of palladium for hydrogen but enhances the desorption ability of carbon monoxide. At the same time, the synergistic effect between palladium and the second metal is conducive to the activation of carbon dioxide and the regulation of reaction intermediates, promotes the coupling of intermediates, and thus improves the conversion rate of carbon dioxide and the selectivity of low-carbon mixed alcohols, which is significantly improved compared to traditional palladium-based catalysts, copper-based catalysts, etc.
[0044] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1This is a high-resolution transmission electron microscopy dark field image (STEM) of the PdCu / TiO2 catalyst prepared in Example 1. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0047] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0048] Example 1 Preparation of palladium copper catalyst and evaluation of catalytic performance
[0049] Dissolve 1g of titanium dioxide P25 and 0.189g of copper nitrate trihydrate (0.05g Cu) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 2.2mol / L) to the above mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to the sum of palladium and copper ions is 10:1. Weigh 0.024g of palladium nitrate dihydrate (0.01g Pd) and dissolve it in 2mL of deionized water, and further slowly add the palladium nitrate aqueous solution to the above solution and stir for 1h. After the mixed solution was centrifuged and washed 5 times with deionized water and ethanol respectively, it was dried at 60°C for 12h to obtain a catalyst powder. Based on the mass of titanium dioxide, the loading amount of palladium nanoparticles is 1wt%, and the loading amount of copper nanoparticles is 5wt%.
[0050] The morphology and composition of the nanoparticles are observed using a transmission electron microscope (TEM) or a high-resolution transmission electron microscope (HRTEM). The particle size of the nanoparticles in the palladium-based catalyst is calculated by observing and calculating the particle size of the metal nanoparticles using a transmission electron microscope (TEM) or a high-resolution transmission electron microscope (HRTEM) and taking the average value. Figure 1 It can be seen that the evenly dispersed bright spots are palladium-copper active bimetallic nanoparticles, confirming that the catalyst structure is palladium-copper nanoparticles evenly distributed on the TiO2 carrier. The average particle size of the palladium-copper active bimetallic nanoparticles is about 4nm. The small particle size of the nanoparticles indicates that they have good dispersion and no obvious agglomeration.
[0051] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, tablets were sieved through 20-40 mesh, hydrogen pre-reduction treatment was carried out before the reaction test, the air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, the reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1.
[0052] Example 2 Preparation of palladium zinc catalyst and evaluation of catalytic performance
[0053] Dissolve 1g of titanium dioxide P25 and 0.182g of zinc nitrate hexahydrate (0.04g Zn) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 1.76mol / L) to the above mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to the sum of palladium and zinc ions is 10:1. Weigh 0.024g of palladium nitrate dihydrate (0.01g Pd) and dissolve it in 2mL of deionized water, and further slowly add the palladium nitrate aqueous solution to the above solution and stir for 1h. After the mixed solution was centrifuged and washed 5 times with deionized water and ethanol respectively, it was dried at 60°C for 12h to obtain a catalyst powder. Based on the mass of titanium dioxide, the loading amount of palladium nanoparticles is 1wt%, and the loading amount of zinc nanoparticles is 4wt%.
[0054] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, tablets were sieved through 20-40 mesh, hydrogen pre-reduction treatment was carried out before the reaction test, the air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, the reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1.
[0055] Example 3 Preparation of palladium iron catalyst and evaluation of catalytic performance
[0056] Dissolve 1g of titanium dioxide P25 and 0.361g of iron nitrate nonahydrate (0.05g Fe) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 2.47mol / L) to the above mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to the sum of palladium and iron ions is 10:1. Weigh 0.024g of palladium nitrate dihydrate (0.01g Pd) and dissolve it in 2mL of deionized water, and further slowly add the palladium nitrate aqueous solution to the above solution and stir for 1h. After the mixed solution was centrifuged and washed 5 times with deionized water and ethanol respectively, it was dried at 60°C for 12h to obtain a catalyst powder. Based on the mass of titanium dioxide, the loading amount of palladium nanoparticles is 1wt%, and the loading amount of iron nanoparticles is 5wt%.
[0057] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, tablets were sieved through 20-40 mesh, hydrogen pre-reduction treatment was carried out before the reaction test, the air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, the reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1.
[0058] Examples 1 to 3 prepared palladium copper, palladium zinc and palladium iron catalysts respectively. Example 1 selected copper as the second metal, and successfully prepared a highly dispersed palladium copper catalyst by a two-step sequential reduction method at a certain amount and concentration of raw materials. Example 2 selected zinc as the second metal, and successfully prepared a highly dispersed palladium zinc catalyst by a two-step sequential reduction method at a certain amount and concentration of raw materials. Example 3 selected iron as the second metal, and successfully prepared a highly dispersed palladium iron catalyst by a two-step sequential reduction method at a certain amount and concentration of raw materials. The distribution of low-carbon mixed alcohol products obtained after the catalytic reaction of carbon dioxide hydrogenation using catalysts of different metals and palladium is different.
[0059] Comparative Example 1
[0060] Dissolve 1g of titanium dioxide P25 and 0.024g of palladium nitrate dihydrate (0.01g Pd) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 0.23mol / L) to the mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to palladium ion is 10:1. Wash with water and ethanol by centrifugation twice, and dry at 60℃ for 12h to obtain catalyst powder.
[0061] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, tablets were sieved through 20-40 mesh, hydrogen pre-reduction treatment was carried out before the reaction test, the air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, the reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1.
[0062] Comparative Example 2
[0063] Dissolve 1g of titanium dioxide P25, 0.361g of iron nitrate nonahydrate (0.05g Fe), and 0.024g of palladium nitrate dihydrate (0.01g Pd) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 2.47mol / L) to the mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to the sum of palladium and iron ions is 10:1. Wash with water and ethanol by centrifugation twice, and dry at 60℃ for 12h to obtain catalyst powder.
[0064] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, tablets were sieved through 20-40 mesh, hydrogen pre-reduction treatment was carried out before the reaction test, the air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, the reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1.
[0065] Comparative Example 3
[0066] Dissolve 1g of titanium dioxide P25 and 0.024g of palladium nitrate dihydrate (0.01g Pd) in 6mL of deionized water and stir evenly. Slowly add an excess of sodium borohydride aqueous solution (concentration of 2.47mol / L) to the above mixed solution and stir for 1h, wherein the molar ratio of sodium borohydride to the sum of palladium and iron ions is 10:1. Weigh 0.361g of iron nitrate nonahydrate (0.05g Fe) and dissolve it in 2mL of deionized water, and further slowly add the iron nitrate aqueous solution to the above solution and stir for 1h. After the mixed solution was centrifuged and washed 5 times with deionized water and ethanol respectively, it was dried at 60°C for 12h to obtain a catalyst powder. Based on the mass of titanium dioxide, the loading amount of palladium nanoparticles is 1wt%, and the loading amount of iron nanoparticles is 5wt%.
[0067] Then the catalytic reaction performance test of carbon dioxide hydrogenation was carried out. The catalytic test conditions were: 0.3g catalyst, pressed and sieved through 20-40 mesh, and hydrogen pre-reduction treatment was carried out before the reaction test. The air velocity was 8000mL / g / h, the pretreatment conditions were 200℃, and the reduction was 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor to evaluate the reaction performance. The reaction temperature was 250℃, the reaction pressure was 3MPa, the total air velocity of the raw gas was 6000mL / g / h, and the volume ratio of the gas CO2 / H2 / N2 used was 24:72:4. The reaction performance test results are shown in Table 1. The calculation process of the conversion rate of CO2 and the selectivity of each component is as follows:
[0068]
[0069] Among them, [CO2] inlet and [CO2] outlet Represent the molar concentration of CO2 in the raw gas and tail gas respectively.
[0070]
[0071]
[0072]
[0073] Among them, [CO], [C i H x ]、[C i H x O y ] represent the molar concentrations of CO, hydrocarbons and alcohols products, respectively.
[0074] Table 1 Catalyst activity evaluation results
[0075]
[0076] As can be seen from Table 1, the catalyst prepared by the present invention can better achieve the technical effect of preparing low-carbon mixed alcohols by hydrogenation of carbon dioxide. Taking Example 3 as an example, the conversion rate of carbon dioxide is 26%, and the total selectivity of low-carbon alcohols can reach 55%. Compared with Comparative Example 2, the catalytic performance is improved by nearly 7 times, which also shows that the catalyst prepared by the preparation method of the present invention can effectively regulate the product distribution of low-carbon mixed alcohols. In addition, after changing the reduction order (Comparative Example 3), the performance of the catalyst is greatly reduced compared to Example 3, which also proves the importance and uniqueness of the reduction order in the present invention.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a palladium-based bimetallic nanocatalyst, characterized in that: The following steps are involved: S1. Dissolve the TiO2 carrier and the metal M precursor in a solvent to obtain solution A, wherein the content of M ions is 1wt%-5wt% based on the mass of the TiO2 carrier, and M is one of Cu, Zn, and Fe; dissolve the reducing agent in water to obtain solution B; add solution B dropwise to solution A, stir, and obtain solution C; S2, dissolving a palladium precursor in a solvent to obtain a solution D, wherein the content of palladium ions is 0.5wt%-1wt% based on the mass of the TiO2 carrier; adding solution D dropwise to solution C, stirring, to obtain a mixed solution; S3, washing and drying the obtained mixed solution to obtain a palladium-based bimetallic nanocatalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, when M is Cu, the copper precursor is one or more of copper nitrate, copper chloride, copper sulfate, copper acetylacetonate, copper acetate or hydrates thereof; When M is Zn, the zinc precursor is one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or hydrates thereof; When M is Fe, the iron precursor is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric acetate or hydrates thereof.
3. The preparation method according to claim 1, characterized in that: In step S1, the reducing agent is one or more of ascorbic acid, ammonia borane complex, diborane, ethylene glycol, sodium borohydride, potassium borohydride, and hydrazine hydrate; The concentration of the reducing agent in solution B is 0.2-3 mol / L.
4. The preparation method according to claim 1, characterized in that: The ratio of the molar amount of the reducing agent to the total molar amount of the M ions and the palladium ions is 20:1 to 10:
1.
5. The preparation method according to claim 1, characterized in that: In step S1, the dropping speed is 0.3-1 mL / min, the stirring speed is 500-1200 r / min, and the stirring time is 0.5-3 h.
6. The preparation method according to claim 1, characterized in that: In step S2, the palladium precursor is one or more of palladium acetate, palladium chloride, palladium nitrate, palladium acetylacetonate, and potassium tetrachloropalladate.
7. The preparation method according to claim 1, characterized in that: In step S2, the dropping speed is 0.3-1 mL / min, the stirring speed is 500-1200 r / min, and the stirring time is 0.5-3 h.
8. A palladium-based bimetallic nanocatalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7, the palladium-based bimetallic nanocatalyst comprises a TiO2 carrier and bimetallic nanoparticles loaded on the TiO2 carrier, wherein the bimetallic nanoparticles are Pd and M, and M is one of Cu, Zn, and Fe; the average particle size of the bimetallic nanoparticles is 3-10 nm; Based on the mass of the TiO2 carrier, the loading amount of Pd is 0.5wt%-1wt%, and the loading amount of M is 1wt%-5wt%.
9. Use of the palladium-based bimetallic nanocatalyst according to claim 8 in the preparation of low-carbon mixed alcohols by catalytic reaction of carbon dioxide hydrogenation.
10. The use according to claim 9, characterized in that: The catalytic reaction is carried out in a high-pressure fixed-bed continuous flow reactor, and the reaction conditions are: reaction temperature is 200-400°C, reaction pressure is 2-8MPa, total space velocity of feed gas is 2000-7000mL / g / h, volume ratio of hydrogen to carbon dioxide is 4:1-1:1, and the low-carbon mixed alcohol is methanol, ethanol and propanol; Preferably, the palladium-based bimetallic nanocatalyst needs to be reduced before use, the reduction treatment atmosphere is hydrogen, the hydrogen space velocity is 6000-20000 mL / g / h, the reduction treatment temperature is 200-400° C., and the reduction treatment time is 2-6 h.
Citation Information
Patent Citations
Metal-loaded titanium-based catalyst and preparation method thereof
CN102489295A
Copper-based nano catalyst for preparing high-carbon alcohol from synthetic gas as well as preparation method and application thereof
CN102500374A
Carbon-loaded kernel-shell copper-palladium-platinum catalyst for fuel battery and preparation method thereof
CN102664275A
Carbon black noble metal catalyst preparation method
CN105435808A
Catalyst in process for producing 1, 5-pentanediol from biological furfuryl alcohol through hydrogen ring opening as well as preparation and application of catalyst
CN113877583A
Cited By
Rhodium-iron bimetallic catalyst as well as preparation method and application thereof
CN119588376A
Rhodium-iron bimetallic catalyst, its preparation method and application
CN119588376B